Empirical Casestudy on Approaches to Sampled Control - Burger, Alexandra; Wellhausen, Jens (Institute of Automation and Computer Science, Brno University of Technology, 2017)
Two main approaches on sampled control are compared, the descrete equivalent design and the direct discrete design. Both design methods are used to implement a control system for a real plant, DC-motor. It is shown that discrete equivalent design works well with su cient high sampling rates and that direct discrete design works nearly independent of sampling time.
Keywords: discrete control; PI-controller; state space control; observer; feedforward control; structure with two degrees of freedom